(untitled) (Research, Society and Development, 2021)
Jabuticaba (Plinia jaboticaba (DC) Berg.) is considered one of the most important Brazilian sources of anthocyanins. Very appreciated, its consumption occurs in the fresh forms and as a processed product, such as jellies, liquors and alcoholic fermented beverages. Although popular, the alcoholic fermented is produced as artisanal way, with poor quality control and no standardization. The objective of this work was to characterize chemically the fermented beverage from jabuticaba produced in an artisanal way, being evaluated the pH, content of phenolic compounds, total, monomeric and polymerized anthocyanins, sugars, ethanol, total tannins, antioxidant capacity, color intensity, hue and color composition, ellagic acid content, organic acids, 2,3, -butanediol, glycerin, amino acids, biogenic amines and ammonia ion. From the results, it was possible to characterize the beverages, with emphasis on the concentration of ellagic acid, which was above that normally found in traditional wines. The concentration of lactic acid and biogenic amines indirectly attest to the sanitary quality of the product, an important parameter when it comes to artisanal beverages. With this work is expected to contribute to the possibility of building a quality standard for this type of product.